Design and Development of a Web-Based Point of Sale System for Small-Scale Retail Management - Irsan Ramadhani; Ratih Nindyasari; Alif Catur Murti (Komunitas Dosen Indonesia, 2025)
This study addresses the issue of stock management inaccuracies and sales record discrepancies at Toko Dadi Barokah, primarily caused by manual recording systems. These manual processes often result in mismatches between recorded sales and actual revenue, delayed stock updates, and poor customer service. The objective of this research is to design and implement a web-based point-of-sale (POS) information system to improve operational efficiency and customer satisfaction. The urgency of this study lies in the operational inefficiencies and financial risks associated with manual systems, including delayed inventory updates, misaligned stock levels, and revenue loss due to poor oversight. To overcome these challenges, an integrated system was developed that encompasses inventory management, sales recording, and integration with financial and logistics subsystems. This system was designed using both qualitative and quantitative approaches, with iterative prototyping and user-centered development. The implemented web-based POS system showed significant improvements in the accuracy of stock and sales data, reduced operational errors, and streamlined business processes. Performance evaluation and a comparative case study of similar retail enterprises provided additional insights into system scalability and adaptability. This research contributes to enhancing the operational efficiency of small and medium-sized enterprises (SMEs) by offering a scalable technological solution tailored for limited-resource environments. The findings offer practical implications for similar businesses seeking to leverage digital transformation to improve service quality and competitiveness in increasingly digital retail landscapes.